Assessing contingent convertible bonds for bank recapitalization in Nigeria - Kabir Katata (CBN Journal of Applied Statistics, 2019)
This study estimates the parameters of credit derivatives, equity derivatives and structural models for bank recapitalisation in Nigeria by employing contingent convertibles (CoCos) and using the Nigeria Treasury Bill rate for 2009 as the risk-free rate, estimated recapitalisation requirements for the banks as at 2009 and relevant banks' share prices for 2008 and 2009. The study finds the structural approach as the preferred model for CoCo pricing, as it reported the least pricing errors and also builds asset values of the banks from publicly-available quoted stock prices as well as deposit components of bank's balance sheet information. The study also finds that CoCo bonds are likely to be fully subscribed when issued given the high stock price volatility coupled with high credit spreads in Nigeria. The paper suggests that CoCos could have been issued by the banks to recapitalise themselves without the need for regulatory actions. Therefore, usage of CoCos by banks can reduce the possibility of a bailout with public funds and lessen regulatory actions, if properly implemented, to boost the troubled banks' capital.
Keywords: C52; C58; G13; G21; G28; G32; G33; 330; Contingent convertible bond; bond pricing; structural model; equity derivatives; credit derivatives